PENGGUNAAN KULIT UBI KAYU (Manihot utillisima Pohl) TERHADAP PENYERAPAN LOGAM Fe (III) PADA AIR PAYAU - Delta Rinanda Duda; Syaiful Bahri; Jaya Hardi; Nov Irmawati Inda (KOVALEN: Jurnal Riset Kimia, 2019)
The absorption of Fe (III) metal in brackish water in the Balaroa Village, West Palu District using Cassava peels (Manihot utillisima Pohl) has been carried out. The aim of this study is determining the lifetime of cassava peels (Manihot utillisima Pohl) on the absorption of Fe (III) ions in brackish water. The research was conducted in a simple purification water system. Brackish water was flowed through the simple purification water system containing Cassava peels (Manihot utillisima Pohl) with a volume of brackish water is 10 liters per day (measured flow rate) and been analyzed every 2 days using UV-Vis spectrophotometry for less than 1 month. The results of the study show that cassava peel could be used as biosorbent to absorb and reduce level of Fe (III) ions in brackish water for 2.821 months. The concentration of Fe (III) ions in brackish water in Balaroa Village, West Palu District is 1.666 ppm. Keywords : Fe (III) Ion, Biosorbent, Cassava Peel